2010
DOI: 10.1590/s1677-55382010000500012
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of transcutaneous functional electrical stimulation on urinary incontinence in myelomeningocele: results of a pilot study

Abstract: Purpose: To investigate the efficacy of transcutaneous functional electrical stimulation (FES) on voiding symptoms in children with myelomeningocele (MMC) suffering from neuropathic urinary incontinence. Materials and Methods: Six girls and 6 boys with moderate to severe urinary incontinence secondary to MMC were included. Median age of children was 5.04 (range: 3-11) years. They underwent a urodynamic study (UDS) before and 3 months after FES with special attention to detrusor leak point pressure (DLPP) and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
5
0
4
Order By: Relevance
“…In their study, mean bladder capacity rose from 221 ml pre-treatment to 277 ml [2]. Kajbafzadeh capacity increased in 9 patients [12]. A randomised trial by Laredo et al also demonstrated efficacy of transcutaneous electrical stimulation to the sacral region in the treatment of bladder hyperreactivity in children [13].…”
Section: Discussionmentioning
confidence: 99%
“…In their study, mean bladder capacity rose from 221 ml pre-treatment to 277 ml [2]. Kajbafzadeh capacity increased in 9 patients [12]. A randomised trial by Laredo et al also demonstrated efficacy of transcutaneous electrical stimulation to the sacral region in the treatment of bladder hyperreactivity in children [13].…”
Section: Discussionmentioning
confidence: 99%
“…That 7 patients (70%) showed improvement in daytime urinary incontinence was a promising finding of our study. Considering that the efficacy of IF-ES on pediatric urinary incontinence has already been reported [14], such treatment benefits are attractive merits for patient and parents. An increase in daytime MBC in 3 patients (30%) was also a promising finding.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have reported the safety and efficacy of IF-ES for LUTS [6,12,14,22] and enuresis [8,9] in children, IF-ES is not yet practiced in Korea. The reasons appear to be the limited knowledge of the modality, insufficient trained manpower for this outpatient procedure, and cost problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reuseable nature of the generator makes it cost effective over the long term as well. There are reports of TENS being used for neurogenic voiding dysfunction secondary to myelomeningocele with 9/12 children having improvement on the urinary incontinence score [38]. With regard to non-neurogenic voiding dysfunction, TENS has been used successfully in 42 patients, 50% success at average follow up of 21 months.…”
Section: Cutaneous Neuromodulation (Tens)mentioning
confidence: 99%